Perancangan Corporate Identity Dan Media Promosi PT. Reksa Abadi Bersama Sebagai Upaya Meningkatkan Brand Awareness - Nuzula, Firdha Ramadhani; Budiardjo, Hardman; Riqqoh, Abdullah Khoir (Jurnal Art Nouveau, 2016)
PT. Reksa Abadi Bersama or known as RAB group, is a company that serve in supply material especially for limestone, they hold distribution among Indonesia. The problem is RAB group needs identity design concept that for the identity of the company known by customers, especially hearts sale to all customer. RAB Group is a newborn company and needs identity system design and media to the promotion. That design objectives for the review to know how to design identity media and sale as an attempt to improve customers at brand awareness. Designing using qualitative methods, observation, depth interview, and to review existing studies found the formulation of concept designing. From the data found the findings excellence analisisa products to the audience will be communicated to all customers. Make promotion and design activities corporate identity don’t known reason why the RAB Group excellence unknown. The taxable income processing data analysis found keyword design concept